Study of Runway 3 Performance and the Effect of Crossing Taxiway on Runway 2 Capacity at Soekarno-Hatta International Airport - Mokhamad , Bagus Indrawan; Ahyudanari, Ervina (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
Soekarno-Hatta International Airport is the busiest airport in Indonesia, and the number of passengers keeps increasing. Therefore, a larger runway capacity is required due to increased aircraft movements. Soekarno-Hatta International Airport has a new 3000 x 60 meter runway 3 to increase runway capacity by 114 to 120 movements per hour. Runway 3 and Runway 2 are parallel runways where Runway 3 is connected by a crossing taxiway if the aircraft on Runway 3 will head to the terminal. This study analyzed the suitability of parallel runways and the effect of crossing taxiways on the capacity of runway 2. The FAAA method is used in analyzing the length of runway 3, whereas the suitability of the separation distance between runways used the rules of ICAO. The calculation of runway capacity used the time-space analysis method and mathematical simulation modeling with the principle of Air Traffic Separation. The results of the calculation analysis found that the required runway length evaluation of 3200 meters, so the addition needs to be done. A distance of 500 meters is obtained for the runway separation distance analysis. For the non-instrument approach, it has been fulfilled, whereas for the instrument approach, it was not fulfilled. The simulation analysis found that the capacity of runway 2 decreased from 42 to 30 movements, while on runway 3, 29 movements were found. The total movement reached 59 movements. Therefore, the addition of runway 3 only increased flight operations by 17 movements compared to operations using only runway 2.